Investigation of PLGA nanoparticles in conjunction with nuclear localization sequence for enhanced delivery of antimiR phosphorothioates in cancer cells in vitro - Malik, Shipra (J Nanobiotechnology, 2019)
Numerous first generation phosphorothioates (PS) and their derivatives have shown promise targeting mRNA for therapeutic applications and also gained market approval for their use as a drug. However, PS have not been explored for targeting microRNAs (miRNAs or miRs). In particular, efficient delivery remains a critical cog in PS-based antimiR applications. In this study, we tested and characterized a series of poly-lactic-co-glycolic-acid (PLGA) polymers of different molecular weights that can encapsulate the optimum amount of antimiR-155 PS with uniform morphology and surface charge density. We found that nuclear localization sequence substantially increases loading of antimiR-155 PS in PLGA nanoparticles. Further, in a battery of cell culture studies, we confirmed that PLGA nanoparticles encapsulated nuclear localization sequence/antimiR-155 PS combination undergoes significant intracellular delivery and results in reduced expression of miR-155. In conclusion, we successfully demonstrate the feasibility and promise of optimized PLGA nanoparticles based PS delivery in combination with nuclear localization sequence for antimiRs based therapeutics. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12951-019-0490-2) contains supplementary material, which is available to authorized users.